Certificateless Group to Many Broadcast Proxy Reencryptions for Data Sharing towards Multiple Parties in IoTs. (29th June 2022) - Kim, Won-Bin; Kim, Su-Hyun; Seo, Daehee; Lee, Im-Yeong
Abstract : Proxy reencryption delegates encrypted data stored in a proxy to a third party. This proxy reencryption takes the form of one sender providing data to one receiver. However, this method incurs a significant overhead for both the sender and proxy as the number of users receiving the same data increases. In addition, in a large-scale environment, such as an Internet of Things or big data environment, a scenario where several workers jointly create and own an output may exist. In such an environment, ownership disputes can arise when only one operator owns a piece data used by other operators. In this study, to solve this problem, we propose a technique in which multiple users can jointly own one piece of data, and multiple recipients can receive the same data through proxy reencryption.